SOLIDARITY ECONOMY OF SANTA MARIA: A STUDY OF THE SPREAD OF ITS VALUES AND PROFILE OF PARTICIPANTS - Pelegrini, Tatiane; Sanguinet, Eduardo Rodrigues; Lorenzoni, Rodrigo Klein; Dörr, Andréa Cristina; Rossato, Marivane Vestena; Klinger, Ana Carolina Kohlrausch (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/223611708798 Fairtrade emerges as an area where concepts such as sustainability and fair price are applied through initiatives like the Solidarity Fair in Santa Maria-RS, held since 1994, and constitute a field where the values of the Economic Solidarity are spread. This work includes a survey of 30 exhibitors and 55 consumers attending the 5th Fair of Solidarity Economic Mercosur Santa Maria in 2011, in order to characterize the processes and agents involved. The results show that consumers have specific knowledge about economic solidarity, and a high budget constraint and schooling, which allow them to practice a "responsible consumption". For the exhibitors, it was found that they do not spend much time on research on Economics of Solidarity, and have income and education levels below the monthly average consumers who attend the Fair. Most exhibitors also come mostly from municipalities of the Rio Grande do Sul state, noting that disclosure failures occur nationally and internationally. It is concluded that the Economic Solidarity has its own way to expand values, and a growing consumer audience concerned with the development of production forms that spread environmental sustainability and ensure fair prices.